Aging time of five muscles from carcass of Nellore young bulls - Simonetti, Laís Regina; Lage, Josiane Fonseca; Berchielli, Telma Teresinha; Oliveira, Emanuel Almeida; Dallantonia, Erick Escobar; Delevatti, Lutti Maneck (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
ABSTRACT. This trial aimed to assess the qualitative traits of five muscles of 14 Nellore bulls with 450 kg ± 30.7 kg BW, feedlot fed for 60 days. After slaughter and carcass chilling, samples of the Biceps femoris (BF), Longissimus (LD), Gluteus medius (GM), Semitendinosus (ST) and Trapezius thoracis (TT) muscles were collected, vacuum-packed and aged at 0 to 2 ºC for 1, 7 and 14 days and subsequently stored at -20ºC for chemical and quality analysis. The pH, shear force, water holding capacity, cooking losses, meat color and ether extract were evaluated in all aging times. Data were analyzed in a split-plot design using the PROC MIXED procedure of SAS. Aging affected quality traits and chemical properties of the meat, improving aspects, such as tenderness (p < 0.01) and lightness (p < 0.01). The Trapezius thoracis muscle has a higher color stability compared with the Longissimus muscle. Aging is not recommended for the ST muscle because the tenderness is not improved. The GM and BF muscles are tender on the first day, and the aging process is indicated for these cuts for adding value to the beef.

RESUMO. Foram estudadas as características qualitativas de cinco músculos, maturados ou não, de quatorze bovinos da raça Nelore com 450 kg ± 30,7 kg de peso corporal e confinados por 60 dias com dieta contendo 60% de concentrado e 40% de volumoso na MS. Após o abate e resfriamento das carcaças, amostras dos músculos: picanha, (Biceps femoris - BF), contrafilé (Longissimus - LD), alcatra (Gluteus medius - GM), lagarto (Semitendinosus - ST) e acém (Trapezius thoracis - TT) foram retirados, embalados à vácuo e maturados em câmara B.O.D (0 a 2oC) por um, sete e 14 dias e posteriormente armazenadas a -20oC para análises químicas e de qualidade. Os dados foram analisados em um delineamento em split-plot utilizando o procedimento PROC MIXED do SAS. A maturação influencia nas características qualitativas e químicas da carne bovina, melhorando aspectos como a maciez (p < 0,01) e a luminosidade (p < 0,01). O músculo Trapezius thoracis tem uma maior estabilidade de cor quando comparado com o músculo Longissimus. Não é recomendada a maturação do músculo ST em razão deste não apresentar melhora em sua maciez. Os músculos GM e BF apresentam-se macios logo no primeiro dia, sendo que o processo de maturação para estes cortes é indicado em razão de agregar valor à carne.
Maturação de cinco músculos da carcaça de novilhos da raça Nelore
Keywords: beef cattle; biceps femoris; longissimus; meat color; Nellore; tenderness.; bovinos; cor da carne; cortes cárneos; maciez; Nelore; pH